Constructing Gene‐Enhanced Tissue Engineering for Regeneration and Repair of Osteochondral Defects. Issue 8 (27th June 2019) - Chen, Taijun; Cao, Fei; Wu, Xin; Peng, Wenzhen; Zhi, Wei; Weng, Jie; Zhang, Xingdong; Wang, Jianxin
Abstract: In situ sustained release of endogenous growth factors from cells is a challenge for repair and regeneration of tissue. Although recombinant adenovirus vectors are an effective delivery system that can prolong the release of growth factors and is very suitable for the therapy of growth factors, these recombinant adenovirus vectors that are widely used at present have low safety and stability in terms of long‐term expression. In this study, the above problems are solved by knocking out both E1 and E3 genes at the same time and directly inserting the gene fragments encoding target proteins after the inverted terminal repeats. Finally, the combination of gene therapy with tissue engineering in regeneration and repair of full‐thickness defects of osteochondral tissue are applied as an example. The results show that this strategy can achieve complete repair of articular osteochondral defects and recovery of their function, and meanwhile solve the problems of low safety and expression instability of recombinant adenovirus vectors. This method provides a bright prospect for the application of gene enhanced tissue engineering in the regeneration and repair of joint tissue, and also provides a reference for the repair and regeneration of other tissues. Abstract : This work shows the construction of a recombinant adenovirus and its role in osteogenic differentiation in vitro, integration between the newly formed and host osteochondral tissue, repair of the articular osteochondral defect, and recovery of the function of the repaired articular.